Midiatização, algoritmos e plataformas: agenciamento e circulação de emoções no Spotify - Batista, Guilherme Martins (Universidade do Vale do Rio dos Sinos, 2022)
This work arises an anguish due to the lack of information and understanding of the circulation phenomenon (BRAGA, 2007; FAUSTO NETO, 2012; FERREIRA, 2013; 2017) that occurs on the Spotify music streaming platform. Following the three axes of epistemological interface - Communication, Materialities and Semiotics -, the objective of this dissertation was to build the object of study, composed of the individual consumption of profiles on the platform, from the algorithmic management established in this environment, and to recognize what are its conditions of production of meaning (FERREIRA, 2017) considering the algorithmic logics, and what are the limits of suggestion existing in the construction of reality on this platform. By specifying these objectives, it is about: (1) understanding the platform and its activities; (2) recognize the processes in which the experience is given by the consumer; (3) list the evidence that provided the abductive inferences established here; (4) and, finally, to record the conclusions established after two years of investigation on the subject. Unlike the works gathered on mediatization and platform, we understand and explain how the recommendations and information available are, in addition to automatisms and practicalities, constant acts of manipulation on the platform, semiotic assemblages and intensities of significance in addition to a succinctly cultural phenomenon. In this sense, we used Verón's (1989) ethnographic, stratification and topographic methodology, including interviews with consumers, while analyzing, under the mediatization spectrum, the way in which circulation occurs in its mesoanalysis meanders (FERREIRA, 2022). With this panorama of studies, we were able to understand the agency capabilities (DELEUZE and GUATTARI, 2016) of the platform, its construction and constant manipulation in the act of suggestion and interference. The established visibility agency, the suggestive environment and the sensitive strategies (SODRÉ, 2006) conditioned by financial capitalism were the main problematizations that synthesize the tactics of normalization of the platform's interests, using cultural algorithms (FERREIRA, 2021) and impulses of the culture, before being a sociability created for the user. This happens by using the bonds and relationships that affection provides and, therefore, when investigating emotions, we understand that there are limits and impasses when this occurs, mainly due to the lack of understanding of the personal and collective meanings that occur. The decipherings arose from the retrieval of gathered data, interviews and deductive and inductive inferences that the research provided us during this Master's study, aiming to add to the ethical communicational studies of the practical panoramas of the contemporary world from a mediatization look.
Keywords: Midiatização; Algoritmo; Semiótica; Spotify; Mediatization; Algorithm; Semiotics; ACCNPQ::Ciências Sociais Aplicadas::Comunicação